2010
DOI: 10.1016/j.carbpol.2010.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan–pectin multiparticulate systems associated with enteric polymers for colonic drug delivery

Abstract: a b s t r a c tThe great challenge in using native degradable polysaccharides for the development of drug delivery systems is their high aqueous solubility, which may contribute to the undesirable premature and localized release of the drug. Multiparticulate systems showing simultaneously specific biodegradability and pHdependent drug release were prepared based on chitosan (CS), amidated pectin (PC), and calcium ions, using triamcinolone (TC) as model drug. Hidroxypropylmethyl cellulose phthalate (HPMCP) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(26 citation statements)
references
References 27 publications
0
22
0
4
Order By: Relevance
“…Figure 5 shows that the MPs had a moderate swelling in SGF during the first 15 min where the swelling index was $150% and remained at that level for the rest of the study period. At the low pH of SGF, the carboxyl groups of pectin were not ionized, which reduced the repulsive forces among the polymer chains and decreased their swelling (Oliveira et al, 2010). Although chitosan was fully ionized in SGF and could increase the MP swelling, its lower concentration (0.5%) compared to that of pectin (4%) limited its effect on the MP swelling.…”
Section: Microparticle Swelling Behaviormentioning
confidence: 96%
See 1 more Smart Citation
“…Figure 5 shows that the MPs had a moderate swelling in SGF during the first 15 min where the swelling index was $150% and remained at that level for the rest of the study period. At the low pH of SGF, the carboxyl groups of pectin were not ionized, which reduced the repulsive forces among the polymer chains and decreased their swelling (Oliveira et al, 2010). Although chitosan was fully ionized in SGF and could increase the MP swelling, its lower concentration (0.5%) compared to that of pectin (4%) limited its effect on the MP swelling.…”
Section: Microparticle Swelling Behaviormentioning
confidence: 96%
“…Pectin is non-toxic and not affected by gastric or intestinal enzymes while being completely degraded by pectinolytic enzymes produced by microflora in the colon (Bourgeois et al, 2006). The amidated low methoxy (LM) pectin, in which some of the carboxylic acid groups are amidated, is more tolerant to pH variations which makes it an appropriate candidate for the design of colon-targeted drug delivery systems (Oliveira et al, 2010). However, pectin high aqueous solubility and swelling properties are considered the major drawbacks that lead to rapid drug release during transit in the upper GIT (Maestrelli et al, 2008a;Wei et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SD 1:10:10 and SD 1:15:15 exhibited low drug release rates in acid media releasing 19% (± 0.0012) and 37% (± 0.0184) of drug, respectively in 30 min. This behavior can be attributed to the gastro-resistance properties of HPMCP, which exhibited lower swelling in this medium (Table 1), avoiding erosion and contributing to decreasing drug release rates (Oliveira et al, 2010). Indeed, it can be observed despite the presence of HPMCP, an enteric polymer, the drug release rates in the first 15 minutes were very similar for both acid and enteric media.…”
Section: Resultsmentioning
confidence: 72%
“…Increased liquid uptake values in the simulated enteric medium indicated that increases in pH should favor carboxyl group repulsion in HPMCP, causing the chains to move farther apart loosening the polymer matrix. Both of these factors favor the entrance of water molecules (Oliveira et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of CAP and HPMCP resulted in the highest control over the drug release in all media. CAP-Triamcinolone formulation presented the slowest drug release rate, of only 1.33%, in acidic medium after 2h, while the control formulation released 45.52% after the same time 58 . Nanoparticulate colloidal carriers composed of natural or synthetic polymers have also been investigated for colon targeting 59 .…”
Section: 2mentioning
confidence: 91%